Role of endoscopic ultrasound-guided fine needle aspiration biopsies in diagnosing pancreatic neoplasms in the paediatric population - Kebe Radulović, Maja (Radiology and oncology (Ljubljana), 2024)
Background: Endoscopic ultrasound-guided fine needle aspiration biopsy (EUS FNAB) is a well established diagnostic method in adult patients, but is rarely used in the paediatric population. The Clinical Department of Gastroenterology at the University Clinical Centre Ljubljana and the Department of Cytopathology at the Institute of Pathology, Faculty of Medicine, University of Ljubljana, Slovenia, have been closely collaborating on EUS FNAB since the introduction in 2010. The aim of the study was to review the cases of EUS FNAB of pancreatic neoplasms in children. Patients and methods: In the digital archive of the Institute of Pathology (IP), Faculty of Medicine (FM), University of Ljubljana (UL), we found 6 cases of EUS FNAB in children, 3 had EUS FNAB of the pancreas, 2 of whom had a cytopathologic diagnosis of a tumour. In the first case, the lesion was ultrasonographically solid, and the cell sample contained branching papillary structures surrounded by aggregates of small cells with nuclear grooves. In the second case, the lesion was ultrasonographically cystic, and predominantly necrosis was seen, with only single preserved cells. Positive nuclear reaction for ß-catenin was found in both cases by immunohistochemical staining. Results: In both cases, the cytopathological diagnosis of solid pseudopapillary neoplasm of the pancreas was made, the cases represent the totality of paediatric cases of pancreatic neoplasms from the Children's Hospital Ljubljana since 2010. There were no adverse events during and after EUS FNAB. A histopathological examination of the tumour resection specimens confirmed the cytopathological diagnosis. Conclusions: Our experience indicates that EUS FNAB is a safe and effective method for diagnosing pancreatic neoplasms in the pediatric population, as supported by the findings in the literature.
Keywords: aspiracijska biopsija s tanko iglo; endoscopic ultrasound; endoskopski ultrazvok; fine needle aspiration biopsy; neoplazma trebušne slinavke; otroška patologija; paediatric pathology; pancreatic neoplasm